Sosialisasi Pencegahan Cybercrime Untuk Guru SD Negeri 132408 di Tanjung Balai Selatan - Maulina Azmi, Sri Rezki; Siagian, Yessica; Kurniawan, Reza (STMIK Royal, 2025)
The advanced innovation has essentially expanded the danger of cybercrime, driving to issues such as personality robbery, work misfortune, and disturbances to basic framework. In the interim, cybercriminals proceed to create modern procedures and methodologies in committing their criminal acts. The reason to depict the degree of cybercrime dangers in Indonesia. Common cyber dangers in Indonesia incorporate malware assaults, refusal of benefit (DoS), dispersed refusal of benefit (DDoS), and phishing. These dangers are frequently exacerbated by a need of mindfulness and instruction almost cybersecurity and constrained requirement of cybercrime laws. In conclusion, cybercrime dangers in Indonesia are right now considered genuine and profoundly unsafe due to their potential to make national issues. The action was carried out through the arrangement of socialization counseling with address and discourse strategies, as well as address and reply with members. Accommodation of fabric within the frame of control point slides that are displayed amid the action and conveyed to instructors as members . Therefore, it is crucial to recognize the importance of understanding these issues cybercrime anticipation socialization has to be passed on to the educator SD Negeri 132408 di Tanjungbalai Selatan. With this preparing, it is trusted that they can gotten to be web clients who can maintain a strategic distance from the potential to ended up culprits or casualties of cyber wrongdoings. Keywords: cybercrime; socialization; prevention Abstrak: Pengembangan teknologi digital telah secara signifikan meningkatkan risiko cybercrime karena mempengaruhi pencurian identitas, kehilangan tempat kerja, dan infrastruktur kritis. Sementara itu, pelaku cybercrime terus mengembangkan teknologi dan strategi baru untuk inspeksi perilaku kriminal. Ini dilakukan dengan memeriksa dan menganalisis literatur dalam kaitannya dengan dengan cybercrime di Indonesia. Temuan ini menunjukkan bahwa publikasi teknologi dari di Indonesia telah mengambil ancaman terbaru dan dampak pada berbagai aspek kehidupan dan bisnis. Penulis menyimpulkan bahwa cybercrime di Indonesia diklasifikasikan sebagai serius (sangat berbahaya) karena dapat menyebabkan masalah nasional. Kegiatan ini dilakukan dengan pemberian sosialisasi dengan menggunakan metode ceramah dan diskusi, serta bertanya jawab bersama peserta. Bentuk dalam penyampaian materi yaitu slide powerpoint yang dipaparkan dan di edarkan pada saat kegiatan berlangsung. Oleh karena itu, pemahaman mengenai sosialisasi pencegahan cybercrime sangat penting untuk disampaikan kepada para guru di SD Negeri 132408, Tanjungbalai Selatan. Melalui pelatihan ini, diharapkan mereka dapat menjadi pengguna internet yang lebih bijak dan mampu menghindari risiko sebagai pelaku maupun korban kejahatan cybercrime.Kata kunci: cybercrime; sosialisasi; pencegahan